COVID-19 exposures and infection control among home care agencies. (November 2020) - Rowe, Theresa A.; Patel, Mallika; O'Conor, Rachel; McMackin, Sheila; Hoak, Vicki; Lindquist, Lee A.
Highlights: Healthcare Agencies and their frontline caregivers were impacted by COVID-19 early in the pandemic. Caregivers have the ability to inadvertently spread COVID-19 if appropriate infection prevention and control policies are not implemented and followed. Healthcare Agencies need to be included in federal, state, and health system strategies for mitigating the spread of COVID-19. Abstract: Background and objectives: Home care agencies (HCAs) provide caregivers, who perform an important role in maintaining the health and well-being of older adults. However, during the COVID-19 pandemic, paid caregivers had the potential to inadvertently spread COVID-19. We sought to characterize the effects of COVID-19 on HCAs and examine HCAs' infection prevention and control (IPC) policies. Research design and methods: This was a qualitative analysis of data collected from a national survey of HCAs. Surveys were e-mailed to members of a national HCA association on March 18, 2020. Questions included queries on demographics, COVID-19 exposures, effects of COVID-19, and IPC protocols. Results: 1204 HCAs responded with an average census of 96.2 (5−2800) patients daily. Across 36 states, 238 HCAs reported COVID-19 cases or exposures among caregivers. HCAs experienced challenges related to changing patient needs (e.g. decreased caregiver requests), staffing shortages (e.g., fear of COVID-19, inability to train caregivers), and management issues (e.g., inability to obtain supplies). ICP protocols varied in how HCAs followed recommended guidelines, responded to COVID-19 exposures, performed infection surveillance, and implemented precautions. Additionally, HCAs had varying policies for caregiver PTO. Conclusions: HCAs experienced COVID-19 exposures and/or cases early in the pandemic. HCAs identified staffing and PPE shortages, and lack of IPC guidance as challenges. Although caregivers are providing essential care for millions of older adults, they have been largely absent from federal, state, and health system strategies for mitigating the spread of COVID-19. Future policies must include HCAs and their caregivers to optimize care for older adults.